Assessing Endangered Felid Puma concolor Sperm Fertility by In Vitro Fertilization with Domestic Cat Oocytes - Duque Rodriguez, Matteo (2017)
The Puma concolor population has been decreasing during the last 30 years. Semen cryopreservation of this species has been accomplished successfully and offers the possibility of preserving endangered species. We previously showed that fertilizing capability of wild felid spermatozoa can be evaluated using intracytoplasmic sperm injection (ICSI) with in vitro-matured domestic cat oocytes (Moro et al. 2014 Reprod. Domest. Anim. 49, 693-700). Due to the lack of homologous oocytes, we evaluated the capability of the Puma concolor sperm to induce domestic cat oocyte fertilization and subsequent pre-implantation embryo development. In the present study, cryopreserved sperm obtained by electroejaculation from five different males were used for IVF of in vitro-matured (IVM) domestic cat oocytes. Straws were thawed by exposing them to air for 10 s and then immersing in a 37°C water bath for 30 s. The contents of the straws were poured into a sterile 1.5-mL microtube pre-warmed to 37°C. The sperm suspension was diluted (1:3 v/v) by the slow (drop-by-drop) addition of a modified Tyrode’s solution. For IVF, IVM oocytes (n = 370) were co-incubated with 0.5 × 105 motile spermatozoa mL−1 in an atmosphere of 21% O2 in air at 38.5°C for 18 to 20 h. Presumptive zygotes were cultured in vitro in 50-μL drops of modified Tyrode’s medium on 6.5% CO2 in air at 38.5°C. Cleavage was determined at 48 h post-fertilization, and 5% FBS was added at Day 5 of in vitro culture. Blastocyst stage was evaluated at Day 8. Results (mean ± SEM) showed a high cleavage rate (179/370, 49.0 ± 4.0%), and a high development to morula stage (137/370, 34.4 ± 7.2%), and to blastocyst stage (94/370, 23.4 ± 4.7%) for all males. These results indicated that Puma concolor spermatozoa can induce domestic cat oocyte activation and development to blastocyst stage in similar rates to domestic cat homologous IVF: IVM oocytes (n = 291), cleavage rate (199/291, 67.1 ± 6.1%), development to morula stage (144/291, 47.8 ± 4.9%), and to blastocyst stage (86/291, 30.1 ± 1.6%). In conclusion, we demonstrated that domestic cat oocyte can be used to evaluated cryopreserve sperm samples from another felid species.